Exploring Communication Anxiety in English Language Learning through Affective Filter Theory: Evidence from Indian College Students - Udhayachandran, R; Sreenivasulu, Yadamala (Journal of Cultural Analysis and Social Change, 2025)
This conceptual review explores the role of communication anxiety in English language learning among Indian college students through the theoretical lens of Stephen Krashen’s Affective Filter Hypothesis. Drawing on literature published between 2020 and 2025, alongside foundational works in second language acquisition (SLA), the study investigates how emotional variables such as anxiety, motivation, and self-confidence impact learners’ ability to acquire and use English effectively. Key themes identified include the fear of grammatical errors, peer judgment, low self-esteem, and classroom performance pressure, factors that collectively raise the affective filter and inhibit language input processing. The review further examines how supportive teaching practices, empathetic classroom environments, and affective awareness can help lower the filter, enhancing communicative competence. The findings have important implications for English language educators, curriculum developers, and researchers aiming to reduce affective barriers in SLA contexts. This paper calls for more empirical work exploring communication anxiety in multilingual settings and proposes affective, pedagogically informed interventions for improving learner outcomes.